2013
DOI: 10.1128/iai.01181-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Distinct Host Response Profile to Pneumocystismurina Asci during Clearance of Pneumocystis Pneumonia

Abstract: ؉ T cell influx and expression of macrophage inflammatory response markers. A more robust cellular response was also observed in the untreated mice, with increased numbers of macrophages and neutrophils that were associated with greater lung damage. Markers of a Th17 response were also elevated in the untreated mice. These results suggest that the host mounts unique responses to asci and trophic forms. That these 2 life cycle stages provoked distinct host response profiles has significant implications for clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
4
26
1
Order By: Relevance
“…These data indicate that ␤-glucan-and Dectin-1-mediated signals contribute to hypoxemia during Pneumocystis IRIS, consistent with recent observations implicating the ␤-glucan-rich ascus in producing a proinflammatory response (56). Possible mechanisms of inflammatory exacerbation include induction of IL-8 secretion and activation of the IL-23/IL-17 axis by Pneumocystis ␤-glucan (59,60), as well as the effects of Dectin-1 signaling on Th1 and Th17 differentiation of CD4 ϩ T cells (33,56,61,62), which have been shown to contribute to the risk for IRIS (63,64). Although intracellular staining of PMA-and ionomycin-stimulated lung cells did not reveal a strong Th17 signature (see Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These data indicate that ␤-glucan-and Dectin-1-mediated signals contribute to hypoxemia during Pneumocystis IRIS, consistent with recent observations implicating the ␤-glucan-rich ascus in producing a proinflammatory response (56). Possible mechanisms of inflammatory exacerbation include induction of IL-8 secretion and activation of the IL-23/IL-17 axis by Pneumocystis ␤-glucan (59,60), as well as the effects of Dectin-1 signaling on Th1 and Th17 differentiation of CD4 ϩ T cells (33,56,61,62), which have been shown to contribute to the risk for IRIS (63,64). Although intracellular staining of PMA-and ionomycin-stimulated lung cells did not reveal a strong Th17 signature (see Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Previous rodent studies have indicated that a purified Pneumocystis ascus preparation induces inflammation and a fulminant PCP infection (54), whereas echinocandin treatment can selectively ablate the cyst population and prevent transmission of infection (55). Another recent publication by Linke et al has shown that murine hosts mount unique immune responses to the different life forms of P. murina and that the ascus can contribute to the detrimental inflammatory response associated with infection and immune reconstitution syndrome (56). As ␤-glucan recognition is a critical component of fungal immunity, we have sought to test the effect of systemic expression of recombinant Dectin-1:Fc fusion proteins on host defense and inflammatory response in a murine model of P. murina infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cysts drive the early recruitment of activated T cells into the alveolar spaces of neonatal mice. Based on previously published reports, we predicted that the absence of cysts in the inoculum of neonatal mice infected with trophic forms would yield a less robust response than infection with a normal mixture of trophic forms and cysts (22). Clearance of Pneumocystis organisms requires the generation of effective adaptive immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that treatment of mice with the ␤-1,3-D-glucan synthase inhibitor anidulafungin resulted in depletion of P. murina cysts (22). The mice were able to control the remaining trophic burden in the absence of an excessive inflammatory response; however, the details of how trophic forms are recognized and cleared are not known.…”
mentioning
confidence: 99%
“…Therefore, caspofungin and TMP/SMZ used in combination may inhibit the entire life cycle of Pneumocystis jirovecii. Alternatively, caspofungin may decrease β-glucan induced excessive inflammatory responses by inhibiting β-glucan synthesis (20), thus alleviating PCP. Finally, TMP/SMZ acts slowly, requiring 5-8 days to induce a curative effect (1), whereas caspofungin has a rapid onset, therefore it may be inferred that combinational treatment with TMP/SMZ and caspofungin may compensate the TMP/SMZ deficiency that occurs in patients receiving delayed PCP treatment.…”
Section: Discussionmentioning
confidence: 99%